The Role of Agricultural Sector Development Strategy in the Diversification of Algerian Exports: -An Econometric Analytical Study (2000-2023)- - NADJOUA Djedioui; SALAH-EDDINE Mansouri (Dirassat Journal Economic Issue, 2025)
This research investigates the role of export diversification within the framework of agricultural sector development as a means to enhance Algeria’s economic growth from 2000 to 2023. It explores the theoretical foundations of export diversification and evaluates Algeria’s diversification strategy by analyzing the contribution of key economic sectors (industry, tourism, and agriculture) alongside the Hirschman-Herfindahl index. The study examines the agricultural sector’s influence on export diversification through essential variables, including value addition, employment generation, public agricultural expenditure agricultural financing, and agricultural exports. The findings indicate that Algeria’s macroeconomic strategy plays a significant role in strengthening the agricultural sector and expanding exports. Furthermore, a relationship exists between agricultural sector dynamics and export diversification in both the short and long run within the Algerian economy.